Effects Of Storage Container and Storage Condition on Seed Health Quality of Common Bean Variety Ennepa in Southern Ghana (Journal of Science and Technology, 2024)
Common bean (Phaseolus vulgaris L.) has been introduced in Ghana for cultivation; however, yields on farmers’ fields are low due to poor seed health quality resulting in poor plant stand. This study determined the effect of storage containers (polythene bag vs plastic container) and storage environment (ambient vs cold storage temperature) on the seed health quality of common bean seeds stored for eight months. The fungal species and loads on the seeds were determined using the blotter method at 0, 2, 4, 6, and 8 months after storage. Aspergillus spp., Penicillium spp., and Rhizopus spp. were the major fungi recorded during storage. Seeds stored in plastic containers under an ambient environment showed a significantly lower incidence of Aspergillus flavus than the other treatments. Seeds stored in polythene bags under an ambient environment significantly lowered the incidence of A. niger. Seeds stored in polythene bags recorded a significantly higher incidence of Penicillium spp. after two months in storage irrespective of the storage condition. The lowest incidence of Rhizopus spp. was observed in seeds stored in plastic containers in an ambient environment. There was no observed insect infestation in storage over the eight-month duration. Seeds of the common bean variety Ennepa can safely be stored in a polythene bag under an ambient environment (25.43-29.660C).